Food Safety and Standards Act, 2006 (Act No. 34 of 2006, dt 23-8-2006) - Edited by Virag Gupta (New Delhi Commeercial Law Publishers (India) Pvt. Ltd., 2025)
Food Safety and Standards Act, 2006 (Act No. 34 of 2006, dt 23-8-2006)
Keywords: Legal Affairs